Contemporary risk factors associated with ischemic heart disease in central South Africa: a single center study - Butler, Michelle Louise (Central University of Technology, 2022)
Introduction: The study aimed to investigate modifiable and non-modifiable risk factors in coronary artery disease (CAD) patients in central South Africa. Methods: Patients with angiographically confirmed CAD evaluated in the catheterization laboratory for the first time over a two-year period (2016-2017) were included. Data was extracted from the patient’s medical records. Results: Four-hundred-and eighty-two patients met the inclusion criteria, presenting at a mean age of 58.4±10.8 years and were predominantly male (66%). Female patients presented significantly older than males (60.3±9.6 vs 57.4±11.1 years; p<0.05). The mean age at presentation was comparable between ethnic groups, with only Asians presenting significantly younger than Caucasians (49.8±10.5 vs 59.1±10.8; p<0.05). Hypertension (91%) was the most common risk factor, followed by smoking (67%) and obesity (40%). Black Africans demonstrated a higher incidence of hypertension when compared to Caucasians (96% vs 87%; p<0.05). Smoking was more prevalent in Caucasians than Black Africans (68% vs 54%; p<0.05) and occurred more commonly in males than females (73% vs 55%; p<0.05). Most patients presented with acute coronary syndrome (ACS) (72%), mainly with ST-elevated myocardial infarction (STEMI) (36%). The majority of patients presenting with ACS were in the age interval 51-60 years. The ACS risk factor profile was similar to the total study group. Conclusion: CAD is present in all ethnic groups, and modifiable and non-modifiable risk factors are similar to the classical risk factors described worldwide. Minor interracial differences were observed and hypertension was the most prevalent risk factor recorded in central South Africa. Most patients with CAD presented with ACS, particularly STEMI.
Thesis (Master: Health Sciences: Clinical Technology (Cardiology))--Central University of Technology
Keywords: Coronary artery disease (CAD); Cardiovascular disease (CVD); Modifiable risk factors; Non-modifiable risk factors; Acute coronary syndrome